AN ANALYSIS OF DIRECT AND INDIRECT SPEECH ACTS BETWEEN THE MAIN CHARACTERS IN “WHITE CHICKS” FILM - Salsabila, Oviya Talitha; Mahmud, Murni (ELITERATE : Journal of English Linguistics and Literature Studies, 2021)
This findings of the study title is “An Analysis of Direct and Indirect Speech Acts between the Main Characters in ‘White Chicks’ Film” In analyzing this film used theory by Austin (1975) based on speech acts aspects. This research used descriptive qualitative research in order to describe the aspects and its characteristics that are related to the topic. Using the Austin’s theory, the researcher was to find out the relationship between the main characters. The researcher was categorized the characteristic among the characters based of several aspects from Austin theory of speech acts. The results of this study indicates that there is 1 aspect to maintain the relationship between the main characters. They are 11 typical characteristics based on speech acts theory from Austin. Based on the results of this research, the researcher able to classify the characteristic among the characters.